2021
DOI: 10.1186/s13059-020-02237-3
|View full text |Cite
|
Sign up to set email alerts
|

BlastFrost: fast querying of 100,000s of bacterial genomes in Bifrost graphs

Abstract: BlastFrost is a highly efficient method for querying 100,000s of genome assemblies, building on Bifrost, a dynamic data structure for compacted and colored de Bruijn graphs. BlastFrost queries a Bifrost data structure for sequences of interest and extracts local subgraphs, enabling the identification of the presence or absence of individual genes or single nucleotide sequence variants. We show two examples using Salmonella genomes: finding within minutes the presence of genes in the SPI-2 pathogenicity island … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Clade-C contains 2 nalidixic acid-resistant, but ciprofloxacin-susceptible ST198 isolates, whereas clade-D contains 2 ciprofloxacin-resistant ST198 isolates (Figure 1) and these clades correlate with PFGE cluster-A2 (Supplementary Figure 1). These results suggest that the population of Flu R S. Kentucky ST198 is comprised of multiple genetically divergent lineages, which corroborates with published reports (Sukhnanand et al, 2005;Timme et al, 2013;Haley et al, 2016;Tasmin et al, 2017;Luhmann et al, 2021). Epidemiologic source tracing revealed that 11 out of 15 (73%) Flu R S. Kentucky clinical isolates within PFGE cluster-A2 originated from patients with a history of travel to different international destinations before the onset of illness (Table 1).…”
Section: International Travelsupporting
confidence: 90%
See 2 more Smart Citations
“…Clade-C contains 2 nalidixic acid-resistant, but ciprofloxacin-susceptible ST198 isolates, whereas clade-D contains 2 ciprofloxacin-resistant ST198 isolates (Figure 1) and these clades correlate with PFGE cluster-A2 (Supplementary Figure 1). These results suggest that the population of Flu R S. Kentucky ST198 is comprised of multiple genetically divergent lineages, which corroborates with published reports (Sukhnanand et al, 2005;Timme et al, 2013;Haley et al, 2016;Tasmin et al, 2017;Luhmann et al, 2021). Epidemiologic source tracing revealed that 11 out of 15 (73%) Flu R S. Kentucky clinical isolates within PFGE cluster-A2 originated from patients with a history of travel to different international destinations before the onset of illness (Table 1).…”
Section: International Travelsupporting
confidence: 90%
“…Comparative genomics analysis of a large collection of S. Kentucky isolates in this study also confirmed that ST152 and ST198 form two distinct genetic lineages. While others have reported that ST152 and ST198 are genetically distinct (Sukhnanand et al, 2005;Timme et al, 2013;Haley et al, 2016;Tasmin et al, 2017;Luhmann et al, 2021), lineage-specific genetic polymorphisms that clearly distinguish these two lineages have not been identified and described well. Thus, we aimed 2).…”
Section: International Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2632, 1158 and 1379 fully assembled genomes were downloaded from NCBI Reference Sequence Database 33 , 60 (RefSeq; accessed on 15 April 2021), NCBI’s GenBank 34 (accessed on 15 April 2021), and EnteroBase (accessed on 27 April 2021) 35 , respectively. The EnteroBase repository was screened for bla NDM using BlastFrost (v1.0.0) 61 allowing for one mismatch. In addition, we used the Bitsliced Genomic Signature Index (BIGSI) tool (v0.3) 62 to identify all SRA unassembled reads that carry the bla NDM gene.…”
Section: Methodsmentioning
confidence: 99%
“…Others exclusively focus on protein alignment ( Buchfink et al , 2015 ; Suzuki et al , 2015 ; Vaser et al , 2016 ; Zhao et al , 2012 ). Recently, the tool BlastFrost ( Luhmann et al , 2021 ) appeared, which enables sequence queries on a pangenome graph. However, it does not calculate alignments.…”
Section: Introductionmentioning
confidence: 99%